PEMBELAJARAN VIA WHATSAPP (WA) ALTERNATIF MENGATASI PROBLEMIK PEMBELAJARAN DALAM SITUASI PENDEMI COVID 19 DI KELAS PGMI SEMESTER 4 - Nazri Adlani; Maria Hanifah (Universitas Islam Lamongan, 2020)
This study discusses about whatsapp (WA) alternatives media to overcome learning problems in COVID 19 situation. The research was implemented at IAIN Takengon Semester IVth PGMI Class. This research is motivated by learning that stopped due to the COVID 19 epidemic, understanding of technological advances that are still limited in remote areas of the Indonesian homeland, whatsapp as a medium used by the public, in general, has spread throughout the groundbreaking homeland. The research method used was a descriptive qualitative method with a triangulation of research instruments. The results obtained were divided into three sub-topics. (1) The steps of the learning process using the WA feature are the same as learning in class face to face, namely greetings, delivery of learning objectives, delivery of motivation, opening with an attendance, applying learning methods, and closing by praying and giving assignments or further material. (2) WA features that can be used in learning and its use processes are short messages, videos, pictures, file documents, and voice messages. (3) Evaluation of learning that can be done using WA media, namely Question and Answer, working on the pretest/posttest with the specified time, then sending the results of the work through the personal WA, Presentation, and Discussion; Paper Making; Electronic Book Analysis Making.